2020
DOI: 10.1002/lno.11410
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methane ebullition variability across space and time in a Brazilian reservoir

Abstract: The potent greenhouse gas methane (CH 4 ) is readily emitted from tropical reservoirs, often via ebullition (bubbles). This highly stochastic emission pathway varies in space and time, however, hampering efforts to accurately assess total CH 4 emissions from water bodies. We systematically studied both the spatial and temporal scales of ebullition variability in a river inflow bay of a tropical Brazilian reservoir. We conducted multiple highly resolved spatial surveys of CH 4 ebullition using a hydroacoustic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 52 publications
3
51
0
Order By: Relevance
“…From a well‐studied inflow‐bay in CDU and from the main inflow in FUN, we calculated the water volumes of the river‐inflow areas (i.e., the part of the bay which we assumed to be under the influence of the incoming river of this bay) using the surface volume tool in ArcGIS. In CDU, we delimited the river‐inflow area from the non‐inflow (i.e., lake‐like) reservoir area based on field observations of water flow during 15 field campaigns over one year in a northern bay with river inflow (Linkhorst et al., 2020) (Figure S7: river inflow 6); downstream of the placed delimitation, we could not observe a visible unidirectional flow of surface water, and assumed that this corresponds to the end of the river inflow area. In FUN, we delimited the river inflow area behind a large lateral land dam, that is, a levee, at a shallow sill in the main stem in the northernmost large bend of the reservoir (Figure S8: river inflow 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a well‐studied inflow‐bay in CDU and from the main inflow in FUN, we calculated the water volumes of the river‐inflow areas (i.e., the part of the bay which we assumed to be under the influence of the incoming river of this bay) using the surface volume tool in ArcGIS. In CDU, we delimited the river‐inflow area from the non‐inflow (i.e., lake‐like) reservoir area based on field observations of water flow during 15 field campaigns over one year in a northern bay with river inflow (Linkhorst et al., 2020) (Figure S7: river inflow 6); downstream of the placed delimitation, we could not observe a visible unidirectional flow of surface water, and assumed that this corresponds to the end of the river inflow area. In FUN, we delimited the river inflow area behind a large lateral land dam, that is, a levee, at a shallow sill in the main stem in the northernmost large bend of the reservoir (Figure S8: river inflow 1).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous comparison of spatial and temporal variability in CDU (Linkhorst et al, 2020) suggested to sample each hydrological season (rising and falling water level) for annual upscaling of CH 4 ebullition. In LINKHORST ET AL.…”
Section: Temporal Variability Of Ch 4 Ebullitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined gas diffusive fluxes without regard to ebullition since a previous study reported it is the main emission pathway within the reservoir for CO 2 (89%) and for CH 4 (76%) (Abril et al, 2005). Yet the spatiotemporal variability of the ebullitive CH 4 flux has not been accurately addressed at Petit‐Saut while the contribution of such a pathway to the total gas emissions by the reservoir likely exhibits high spatial and temporal variability (e.g., DelSontro et al, 2011; Linkhorst et al, 2020). In particular, ebullition may be an important emissions pathway notably in littoral and transition areas and therefore may exhibit a similar spatial variation to the diffusive flux that we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…gain knowledge on how to best distribute measurement effort between spatial and seasonal coverage (Linkhorst et al, 2020;Wik et al, 2016).…”
Section: 1029/2020jg006014mentioning
confidence: 99%